2007
DOI: 10.1080/14756360701424959
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microwave irradiation on enzymatic properties: applications in enzyme chemistry

Abstract: Although microwave-assisted reactions are widely applied in various domains of organic chemistry, their use in the area of enzyme chemistry has been rather limited, due to the high temperatures associated with the microwave heating: Because current technology, allows a good control of reaction parameters, several examples of microwave-assisted enzyme chemistry have been reported, using stable and effective biocatalysts (modified enzymes). The purpose of this review is to highlight the applications and studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 37 publications
0
40
0
3
Order By: Relevance
“…The fact that the molar ratio has influenced the transesterification yield in such a significant way may be attributed to a lack of nonthermal effects from the microwave irradiations on the molecular structure of the enzyme [20]. Because ethanol is a highly polar molecule that can easily absorb the energy created by microwaves, the lower the level of ethanol in the reaction medium, the higher will be the energy of the microwaves absorbed by the enzymatic molecule, resulting in some conformational changes in its structure, increasing in this way the enzyme selectivity for the substrate.…”
Section: Factorial Designmentioning
confidence: 97%
See 2 more Smart Citations
“…The fact that the molar ratio has influenced the transesterification yield in such a significant way may be attributed to a lack of nonthermal effects from the microwave irradiations on the molecular structure of the enzyme [20]. Because ethanol is a highly polar molecule that can easily absorb the energy created by microwaves, the lower the level of ethanol in the reaction medium, the higher will be the energy of the microwaves absorbed by the enzymatic molecule, resulting in some conformational changes in its structure, increasing in this way the enzyme selectivity for the substrate.…”
Section: Factorial Designmentioning
confidence: 97%
“…Microwave irradiation also offers a fast, easy route to biodiesel production using acid or base catalysts; a satisfactory transesterification conversion can be achieved in a few seconds under microwave irradiation, compared to a few hours under conventional heating [11,20]. The microwave-assisted, lipase-catalyzed reaction method is therefore a significant development and several works have already been published showing the advantages of using this kind of heating system [11,13,17,18,20]. However, most of the works covered in the literature are related with commercial available immobilized lipase preparations, in particularly Novozym Ò 435 and Lipozyme [7,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…需要注意的是, 微波对脂 肪酶活力的影响并不明显 [40] . 此外, Lamare 等 [67] 比较了 在反应前和反应过程中两种情况下对脂肪酶微波处理, 结果表明在反应过程中微波处理的脂肪酶稳定性更强. [69] .…”
Section: 场/反应器强化酶促酯类合成unclassified
“…As an example, these effects are used in biocatalysis discipline (Réjasse et al, 2004;2006;Yadav & Borkar, 2009;Souza et al, 2009), DNA hybridization (Edwards, Young, & Deiters, 2009) and the studies that evaluate enzyme stability with the use of microwave irradiation (Rejasse et al, 2007;Young et al, 2008;Izquierdo et al, 2007;Porcelli et al, 1997;La Cara et al, 1999). Recently, Laurence et al (2000), H. Bohr and J. Bohr (2000), Pomerai et al (2003) reported unfolding or structural changes in proteins with microwave irradiations and suggested the inclusion of www.ccsenet.org/ijc…”
Section: Applications In Proteomicsmentioning
confidence: 99%